1993
DOI: 10.3758/bf03198006
|View full text |Cite
|
Sign up to set email alerts
|

Order and duration of stimuli are important determinants of reactivation

Abstract: Prior cuing treatments intended to alleviate the forgetting of a conditioned aversion to an odor were tested with 18-day-old rats. Previous experiments had shown that when such pups were conditioned with the use of a CS-/CS+ procedure, pretest presentation of the CS-or US, but not the CS+, alleviated the forgetting otherwise seen after a 3·h retention interval. In Experiment 1, it was determined that the forgetting was not alleviated if the CS-was either preceded or followed by presentation of the CS+, despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Despite the large difference in the interval between training and priming, the minimum duration of priming actually decreased from 120 s to 1.5 s over this age range. These priming durations fall well within the range of durations that have been used with both animals and human adults (Arnold & Spear, 1993;Deweer & Sara, 1984;Gordon et al, 1979;Musen, 1991;Schacter et al, 1991), indicating that the phenomenon presently observed is neither species nor task specific.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Despite the large difference in the interval between training and priming, the minimum duration of priming actually decreased from 120 s to 1.5 s over this age range. These priming durations fall well within the range of durations that have been used with both animals and human adults (Arnold & Spear, 1993;Deweer & Sara, 1984;Gordon et al, 1979;Musen, 1991;Schacter et al, 1991), indicating that the phenomenon presently observed is neither species nor task specific.…”
Section: Resultsmentioning
confidence: 79%
“…They hypothesized that memory reactivation had begun at the time of exposure to the reactivation stimulus and that once the memory was reactivated, the continued presence of the reactivation stimulus had led to extinction. Similarly, Arnold and Spear (1993) found that exposing 18-day-old rat pups to the CSþ for 5 s or 15 s reactivated their forgotten memory of a learned avoidance response, but exposing them to the CSþ for 30 s did not.…”
mentioning
confidence: 97%
“…Notice that when the texture CS was presented for a shorter period of time and 5 min elapsed between that CS and the intake test, and an alternative tactile stimulus was available during the texture preference tests (group T-I, experiment 1), no effects were obtained in terms of the magnitude of the tasteaversive response. The amount of exposure to a given cue originally involved in the learning situation, the delay existing between re-exposure to this cue and the testing situation, and the similarity between the nature of the elements that define the learning situation and the re-exposure treatment represent critical variables in terms of determining reactivation processes of the memory under analysis (Miller et al, 1991;Moore Arnold and Spear, 1993;Richardson et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of tactile conditioning was also evaluated. Re-exposure to some of the elements that defined the original learning episode were likely to affect the expression of a given conditioned response through processes such as extinction or reactivation of specific memory contents (Miller et al, 1991;Moore Arnold and Spear, 1993;Spear and Riccio, 1994). This experiment was designed to allow us to answer whether CS or US re-exposure facilitates the expression of texture-or tasterelated memories, or both.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, Arnold and Spear (1993) manipulated the duration of a reactivation treatment with 18-day-old rat pups. They conditioned pups to associate a particular odor with foot shock and, 3 hr after training, exposed the pups to the aversive odor for 30 s (the reactivation treatment).…”
mentioning
confidence: 99%